Ethical and legal debates in Irish healthcare : Confronting complexities - Murray, Claire; Donnelly, Mary (Law teacher) (Irish society., 2017)
The Irish health system is confronted by a range of challenges, both emerging and recurring. This collection provides a foundation for ongoing engagement with selected issues in contemporary Irish health contexts. It includes contributions from scholars and practitioners across a range of disciplines. The essays are theoretically informed and are grounded in the realities of the Irish health system, by drawing on contributors' contextual knowledge. The focus of the collection is interdisciplinary and the essays are situated at the intersection between ethics, law, medicine and policy. It draws out the interlinking themes of context and care, rights and responsibilities, regulating research and oversight of decision-making. This book makes an informed and balanced contribution to academic and broader public discourse. It will be of interest to academics and postgraduate students in ethics, law and health and those outside the academic sphere who must engage critically with the issues addressed.